Baseline cortical excitability determines whether TMS disrupts or facilitates behavior - Silvanto, Juha (2008)
Transcranial magnetic stimulation (TMS) is increasingly used to modify brain activity noninvasively and to study brain-behavior relations. However, results can be variable and the conditions that affect the functional efficacy of TMS remain unclear. Here we show that online TMS can either facilitate or suppress perceptual functions depending on the baseline level of activity of the targeted brain region. When TMS was applied over the motion selective region V5/MT during a simple motion detection task, subjects’ motion detection ability was impaired. Similarly, suppression of V5/MT activity using offline 1 Hz rTMS disrupted performance in a subsequent motion detection task. However, paradoxically, online V5/MT TMS had a facilitatory effect on motion detection if V5/MT had been suppressed by offline 1 Hz rTMS prior to the motion detection task. These results demonstrate that TMS can have an unexpected facilitatory effect on behavior when the targeted neural population is in a suppressed state. Our findings provide further evidence for the view that the effects of TMS are modulated by the initial activation state of the targeted neural population.